The role of public health in rare diseases: hemophilia as an example - El-Sayed, Amr A.; Reiss, Ulrike M.; Hanna, Diana; Bolous, Nancy S. (Frontiers in Public Health, 2025)
IntroductionThe role of public health has evolved from addressing infectious diseases to encompass non-communicable diseases. Individuals with genetic disorders and rare diseases constitute a particularly vulnerable population, requiring tailored public health policies, practical implementation strategies, and a long-term vision to ensure sustainable support. Given the prolonged duration and significant costs often associated with these conditions, comprehensive, patient-centered, and cost-effective approaches are essential to safeguard their physical and mental well-being.AimsTo summarize definitions and concepts related to health, public health, rare diseases, and to highlight the role of integrating public health interventions into routine care in improving patient outcomes. Hemophilia was selected as an exemplary rare disease due to its significant lifetime treatment costs and the recent approval and pricing of its gene therapy as the world’s most expensive drug, highlighting the critical importance of public health policies in ensuring equitable access to care and treatment.MethodsA narrative literature review was conducted between July 2023 and December 2024, searching PubMed, Google Scholar, and Google for various topics related to rare diseases, public health, and hemophilia.ResultsPublic health can play an important role in improving the health outcomes of people with rare diseases by implementing conceptual and applied models to accomplish a set of objectives. Over the past two decades, legislative and regulatory support in high income countries (HICs) has facilitated the development and approval of diagnostics and treatments for several rare diseases leading to important advancements. In contrast, many low- and middle-income countries (LMICs) face obstacles in enacting legislation, developing regulations, and implementing policies to support rare disease diagnosis and treatment. More investment and innovation in drug discovery and market access pathways are still needed in both LMICs and HICs. Ensuring the translation of public health policies into regulatory measures, and in turn implementing, and regularly evaluating these measures to assess their effectiveness is crucial. In the case of hemophilia, public health can play a pivotal role.ConclusionEnhancing public health surveillance, policies, and interventions in hemophilia and other rare diseases can bridge data gaps, support access to equitable treatment, promote evidence-based care, and improve outcomes across the socioeconomic spectrum.